Single-Center Prospective Cohort Study on the Histopathology, Genotype, and Postsurgical Outcomes of Patients With Primary Aldosteronism. Issue 3 (September 2021) - Meyer, Lucie S.; Handgriff, Laura; Lim, Jung Soo; Udager, Aaron M.; Kinker, Isabella-Sabrina; Ladurner, Roland; Wildgruber, Moritz; Knösel, Thomas; Bidlingmaier, Martin; Rainey, William E.; Reincke, Martin; Williams, Tracy Ann
Abstract : Unilateral forms of primary aldosteronism are usually surgically treated to remove the source of aldosterone excess. After adrenalectomy, aldosteronism persists in some patients indicating abnormal aldosterone production from the unresected gland. Our objective was to investigate histopathology, genotype, and postsurgical outcomes in a 3-year prospective cohort of surgically treated patients for primary aldosteronism (from 2016 to 2018). The cohort comprised 60 consecutively operated patients categorized with classical or nonclassical histopathologic findings of unilateral primary aldosteronism. In the classical group were 45 solitary aldosterone-producing adenomas or dominant aldosterone-producing nodules; in the nonclassical group were 15 cases of multiple aldosterone-producing micronodules or nodules (12 cases) or aldosterone-producing diffuse hyperplasia (3 cases). The classical group displayed higher baseline plasma aldosterone concentrations (262 versus 155 pg/mL, P =0.008) and an increased aldosterone-to-renin ratio (81 versus 42, P =0.002). A high proportion of the classical group achieved complete biochemical success (97.6% versus 66.7% in the nonclassical group, P =0.002). The nonclassical versus classical group displayed an increased ratio of absolute aldosterone concentration in the contralateral adrenal vein to peripheral vein at adrenal venous sampling (3.8 versus 2.0, P =0.004). Variants in aldosterone-driver genes were identified in 85% of 41 aldosterone-producing adenomas and were excluded in the remaining 15% by CYP11B2 guided next-generation sequencing. There were no differences in clinical or biochemical outcomes in patients with a solitary aldosterone-producing adenoma categorized by KCNJ5 mutation status. In conclusion, adrenals with a nonclassical histopathology of unilateral primary aldosteronism are associated with a higher incidence of postsurgical disease persistence and increased aldosterone production from the unresected adrenal. Abstract : Supplemental Digital Content is available in the text.